Efficacy of idelalisib and rituximab in relapsed/refractory chronic lymphocytic leukemia treated outside of clinical trials. A report of the Gimema Working Group. Issue 3 (26th March 2021) - Rigolin, Gian Matteo; Cavazzini, Francesco; Piciocchi, Alfonso; Arena, Valentina; Visentin, Andrea; Reda, Gianluigi; Zamprogna, Giulia; Cibien, Francesca; Vitagliano, Orsola; Coscia, Marta; Farina, Lucia; Gaidano, Gianluca; et al.
Abstract: Because the efficacy of new drugs reported in trials may not translate into similar results when used in the real‐life, we analyzed the efficacy of idelalisib and rituximab (IR) in 149 patients with relapsed/refractory chronic lymphocytic leukemia treated at 34 GIMEMA centers. Median progression‐free survival (PFS) and overall survival were 22.9 and 44.5 months, respectively; performance status (PS) ≥2 and ≥3 previous lines of therapy were associated with shorter PFS and overall survival (OS). 48% of patients were on treatment at 12 months; the experience of the centers (≥5 treated patients) and PS 0–1 were associated with a significantly longer treatment duration ( p = 0.015 and p = 0.002, respectively). TP53 disruption had no prognostic significance. The overall response rate to subsequent treatment was 49.2%, with median OS of 15.5 months and not reached in patients who discontinued, respectively, for progression and for toxicity ( p < 0.01). Treatment breaks ≥14 days were recorded in 96% of patients and adverse events mirrored those reported in trials. In conclusion, this real‐life analysis showed that IR treatment duration was longer at experienced centers, that the ECOG PS and ≥3 lines of previous therapy are strong prognostic factor and that the overall outcome with this regimen was superimposable to that reported in a randomized trial.